In Silico Screening Hepatitis B Virus DNA Polymerase Inhibitors from Medicinal Plants - Mokhtar Nosrati; Zahra Shakeran; Zainab Shakeran (Majallah-i dānishgāh-i ̒ulūm-i pizishkī-i Arāk, 2017)
Abstract Background: Hepatitis B virus infection (HBV) is a significant global health problem and is a major cause of morbidity and mortality worldwide. Therefore, currently, introducing novel anti Hepatitis B drugs is taken into consideration. This study was planned to in silico screening novel Hepatitis B virus DNA polymerase inhibitors from two medicinal plants Terminalis chebula and Caesalpinia sappan. Materials and Methods: This is a descriptive-analytic study. In the study, three-dimensional structure of the Hepatitis B virus DNA polymerase was predicted using homology modeling method. A set of phytochemicals from mentioned plants were retrieved from Pubchem database in SDF format. In silico screening was carried out using molecular docking between mentioned phytochemicals and modeled polymerase by iGemdock 2.1 software. Results: Results of the study confirmed that all evaluated ligands have appropriate interactions to the polymerase with least toxicity and without genotoxicity potential. Results also showed that most interactions occur in reverse transcriptase domain which located in 354-694 area in the amino acid sequence of tested polymerase. Analysis of energy and amino acids involved in ligand-polymerase interaction revealed that Terchebin, Chebulinic Acid and Terflavin A have more effective interaction with the polymerase in compared to other ligands. Conclusion: Based on the results it can be concluded that evaluated compounds could be good candidates for in vitro and in vivo research in order to develop novel anti- Hepatitis B drugs.